Neurobiology of Brain Disorders 2015
DOI: 10.1016/b978-0-12-398270-4.00032-x
|View full text |Cite
|
Sign up to set email alerts
|

Disorders of Higher Cortical Function

Abstract: Any queries or remarks that have arisen during the processing of your manuscript are listed below and are highlighted by flags in the proof. (AU indicates author queries; ED indicates editor queries; and TS/TY indicates typesetter queries.) Please check your proof carefully and answer all AU queries. Mark all corrections and query answers at the appropriate place in the proof (e.g., by using on-screen annotations in the PDF file http://www.elsevier.com/book-authors/science-and-technology-book-publishing/ overv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 56 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…Ideomotor limb apraxia is known to affect skilled, purposeful movements such as those assessed by the JHFT, particularly following a left-hemisphere stroke. 9,35 Of our 110 stroke participants, 20 (12 LHD, 8 RHD) were identified as apraxic. To assess the effect of apraxia on performance, we removed the 20 apraxic participants from our ANOVA and found that the main effect of impairment group [ F (3, 136) = 20.3; P < .0001] remained.…”
Section: Resultsmentioning
confidence: 99%
“…Ideomotor limb apraxia is known to affect skilled, purposeful movements such as those assessed by the JHFT, particularly following a left-hemisphere stroke. 9,35 Of our 110 stroke participants, 20 (12 LHD, 8 RHD) were identified as apraxic. To assess the effect of apraxia on performance, we removed the 20 apraxic participants from our ANOVA and found that the main effect of impairment group [ F (3, 136) = 20.3; P < .0001] remained.…”
Section: Resultsmentioning
confidence: 99%
“…Although UN patients are often unware of contralesional stimuli, several patients have now been documented who show to be able to process implicitly the color, shape, identity, and even meaning of symbols, words, and pictures presented in the affected hemispace (e.g., Làdavas et al, 1993). To account for this surprising dissociation, it has been proposed that the impaired spatial representation of contralesional stimuli is what prevent the other stimulus features, which would be fully and adequately processed, from entering consciousness (Berti and Rizzolatti, 1992; Berti et al, 2015). Consistent with FIT, the lack of spatial coding of contralesional objects would prevent attention from being oriented toward them, thus also preventing the binding of their features and their access to consciousness (Deouell, 2002).…”
mentioning
confidence: 99%
“…Both of these patterns are sometimes observed in patients with paraphasic disorders, like fluent aphasia (Berti et al, 2015). In particular, one symptom of Wernicke's Aphasia is the use of jargon speech: long streams of words with seemingly no meaning but retaining some phonological and grammatical structure.…”
Section: Resultsmentioning
confidence: 99%